2018
DOI: 10.1016/j.jtos.2018.07.005
|View full text |Cite
|
Sign up to set email alerts
|

The immunoregulatory role of corneal epithelium-derived thrombospondin-1 in dry eye disease

Abstract: Our study elucidates the function of epithelium-derived TSP-1 in inhibiting DC maturation and shows its translational potential to limit corneal epitheliopathy in DED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 45 publications
(53 reference statements)
1
19
0
Order By: Relevance
“… 87 In a mouse model of DED, it has been observed that TSP-1 levels were increased in the cornea. 88 Moreover, recombinant TSP-1, administered topically, decreased expression of proinflammatory cytokines (IL-1β, IL-6, IL-23, IL-17A) in the conjunctiva and in the cornea, and ameliorated disease severity. Moreover, topical TSP-1 significantly suppressed corneal dendritic cell maturation.…”
Section: Novel Emerging Therapies For Ded Acting Through Other Mechanmentioning
confidence: 99%
See 1 more Smart Citation
“… 87 In a mouse model of DED, it has been observed that TSP-1 levels were increased in the cornea. 88 Moreover, recombinant TSP-1, administered topically, decreased expression of proinflammatory cytokines (IL-1β, IL-6, IL-23, IL-17A) in the conjunctiva and in the cornea, and ameliorated disease severity. Moreover, topical TSP-1 significantly suppressed corneal dendritic cell maturation.…”
Section: Novel Emerging Therapies For Ded Acting Through Other Mechanmentioning
confidence: 99%
“…Moreover, topical TSP-1 significantly suppressed corneal dendritic cell maturation. 88 Within this frame, TSP-1 could represent an interesting innovative approach for DED treatment. Nevertheless, to date, no clinical trials are ongoing to evaluate the effects of TSP-1 for DED treatment.…”
Section: Novel Emerging Therapies For Ded Acting Through Other Mechanmentioning
confidence: 99%
“…Thrombospondin-1 (TSP-1) activates TGF-β, which plays an immunomodulatory role at the ocular surface [129]. Tan et al [130] found that TSP-1 levels are upregulated in the corneas of mice with DED, and interestingly, expression of MHC II by bone-marrow-derived DCs (BMDCs) decreased significantly following co-culture with epithelial cells from DED mice. Further addition of recombinant (r)TSP-1 potentiated the suppressive effect of epithelial cells on BMDC maturation, whereas TSP-1 blockade ameliorated this effect.…”
Section: Emerging Ded-treatment Strategiesmentioning
confidence: 99%
“…For example, following corneal injury, TSP-1 expression is observed in the stroma (where it is usually undetectable) underlying the wounded epithelium at 24 hours post-injury, and reaches peak expression after approximately one week [59]. In experimental DED, exposure to a desiccating environment increases corneal epithelial expression of TSP-1 [62]. Interestingly, Soriano-Romani and colleagues have reported that the expression of TSP-1 by conjunctival fibroblasts is decreased after in vitro stimulation with IL-1β in serum-free culture conditions, although this effect was not observed in serum-supplemented cultures [63].…”
Section: Distribution Of Tsp-1 In Ocular Surface Tissuesmentioning
confidence: 99%